Case Report: Ranula and Sublingual Glands Extirpation as Intraoral Ranula Procedures - Rizki Saputra; Sukri Rahman; Pamelia Mayorita (Journal of Agromedicine and Medical Sciences, 2022)
Ranula is a cystic lesion that develops from saliva extravasation caused by trauma to the sublingual gland or the occurrence of duct blockages. The ranula is divided into intraoral (simple ranula) and plunging ranula. There are several options of methods in the management of ranulas such as sclerotherapy, marsupialization, and extirpation with or without gland removal involved, incision and drainage with intraoral approach, excision lesions with the extra-oral approach. A case of ranula was reported in a girl aged 12 years diagnosed with intraoral ranula (simple ranula). Treatment is done by performing ranula extirpation accompanied by the removal of the sublingual gland and its ducts. The extirpation of the ranula followed by removal of the involved sublingual salivary gland gave satisfactory results with no recurrence until 1 year of follow-up on the management of intra-oral ranula. Keywords: ranula, simple ranula, intraoral ranula